การศึกษาเปรียบเทียบนวนิยายจีน เจีย กับฉบับแปลภาษาไทย บ้าน - ติยานนท์, ณัฐนันท์ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2016)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษากระบวนการถ่ายทอดตัวบทจากนวนิยายจีน เจีย สู่ฉบับแปลภาษาไทย บ้าน ผลการวิจัยพบว่าประการแรกในด้านโครงสร้างทางภาษาทั้งระดับคำและระดับประโยคมีการเพิ่มเติม ตัดทอน ปรับคำหรือข้อความนั้นให้สอดคล้องกับบริบทและการถ่ายทอดตัวบทที่ตรงเกินไป ประการที่สองกลวิธีทางภาษาที่โดดเด่นในนวนิยายจีน เจีย นั้นเป็นการใช้ภาษาภาพพจน์ (figurative language) มีหลายวิธีด้วยกัน อาทิ อุปมา อุปลักษณ์ บุคลาธิษฐาน สัญลักษณ์ สัทพจน์และอติพจน์ซึ่งสามารถอธิบายตามความหมายและโครงสร้างภาษาจีน หรือการปรับเปลี่ยนคำหรือโครงสร้างใหม่โดยให้สอดคล้องกับภาษาไทย ประการที่สามภูมิหลังทางสังคมวัฒนธรรมที่แตกต่างกันของแต่ละชาติมีอิทธิพลต่อการถ่ายทอดความหมายหรือที่เรียกว่า “เอกลักษณ์” ทางภาษา A Comparative Study of Chinese Novel JIA and Its Thai Translation BAAN The purpose of this research was to study the process of conveying the theme in the Chinese novel Jia to its Thai translation Baan, According to the results of this research, it found that the conveying of theme in terms of words and messages was done with addition, reduction, adjustment, and literal translation of both words and messages in order to make the theme comply with the contexts. Next, the figurative languages such as simile, metaphor, personification, symbols, onomatopoeia, and hyperbole are the outstanding language techniques used in the novel Jia. These techniques helped convey the meanings as to Chinese language structure, and adjust the words or structures that were in compliance with Thai. Finally, the different cultural and social backgrounds of different nations had influences on the ways to convey the meanings, which is called "identity" of language.